Communication Accessibility:: 10 answers to 9 questions - Neves, Joselia (Journal of Audiovisual Translation, 2025)
This paper reconceptualises accessibility within Audiovisual Translation (AVT) by introducing the broader notion of Communication Accessibility (CA). Accessibility for communication purposes is examined through a constructivist lens, which views it not merely as a technical solution but as a fundamental component of effective communication. It is argued that accessibility and translation are inherently linked as enabling practices that facilitate interaction with the world, in all its dimensions. The paper charts the evolution of accessibility from a niche concern within AVT to the dynamic, interdisciplinary field of Communication. While traditional modes like subtitling and audio description continue to be essential for persons with specific needs, the field now explores a multi-multi approach which takes accessibility beyond disability-focused solutions. Innovations in technology, creative practice and multisensory engagement are drivers of this transformation, extending accessibility toward user-centred design and inclusive participation. The role of academia is emphasised in bridging theory and practice, while preparing professionals for new roles and increasingly interdisciplinary demands. The paper concludes by advocating for a paradigm shift: from accessibility as a supplementary assistive service to an integral aspect of communication itself. This shift highlights a fresh take on accessibility, inclusion, and sustainability, positioning CA as vital to fostering meaningful social interaction and progress. Lay summary Making the world accessible to all is a complicated challenge that is hard to define. Recently, accessibility has become a major focus in audiovisual translation studies that has focused on formats like audio description for visually impaired individuals and subtitling for deaf and hard-of-hearing audiences. Researchers are exploring new ways to make media more accessible, such as using easy language or creating multisensory experiences. These innovative methods aim to support people with disabilities but also create experiences that everyone can enjoy. Interestingly, accessibility is starting to be viewed differently: rather than just a support tool, it’s evolving into creative experiences. Scholars suggest that we should look at accessibility through new perspectives to broaden its impact. This paper, written by a researcher who is also an educator and social advocate, tackles some of the key issues in today’s academic discussions. Presented as providing ten answers to nine questions, it concludes by proposing that we view accessibility as a part of Communication Studies, as communication is where people most often encounter barriers.